Kontrast i analogia w reportażu parabolicznym - Frukacz, Katarzyna (Zagadnienia Rodzajów Literackich, 2022)
The paper focuses on various examples of Polish literary reportage which draw upon parable, that is, a didactic story aimed at conveying moral, religious, philosophical, or existential principles by means of allegory, symbolism, and metaphor. The main purpose of the research is to examine the way in which contemporary reporters make use of contrast and analogy as tools for transferring documented facts to a universal level. In the article, the mechanism of parabolization shaped by both these devices is considered first in terms of content of reportage publication, and then with reference to the structure of journalistic narrative. The initial study includes parabolic parallels and antithesis in non-fiction books by Wojciech Jagielski and Katarzyna Surmiak-Domańska. The latter part discusses selected works by Mariusz Szczygieł and Witold Szabłowski regarding transcending literal meanings through the specific segmentation of body text. This dual analysis conducted in the paper is preceded by an introduction, in which the authoress argues the symbiotic relation between the notion of parable, the poetics of contrast, and the principle of analogy. She also presents the origins and development of parabolic reportage in twentieth-century Poland. A special emphasis is placed here on the so-called Aesopian language, which enabled reporters to pass the Communist censorship thanks to hidden political allusions and other features typical of parable. In the conclusion, the parabolic tendency is recognized as still valid in today’s Polish reportage, though different in significance and strictly associated with literary techniques of contrast and analogy.